Evaluation of the sustainability of contrasted pig farming systems: development of a market conformity tool for pork products based on technological quality traits. (8th September 2014) - Gonzàlez, J.; Gispert, M.; Gil, M.; Hviid, M.; Dourmad, J. Y.; de Greef, K. H.; Zimmer, C.; Fàbrega, E.
<x content-type="archive" xml:space="preserve">Abstract</x> A market conformity tool, based on technological meat quality parameters, was developed within the Q-PorkChains project, to be included in a global sustainability evaluation of pig farming systems. The specific objective of the market conformity tool was to define a scoring system based on the suitability of meat to elaborate the main pork products, according to their market shares based on industry requirements, in different pig farming systems. The tool was based on carcass and meat quality parameters that are commonly used for the assessment of technological quality, which provide representative and repeatable data and are easily measurable. They were the following: cold carcass weight; lean meat percentage; minimum subcutaneous back fat depth at m. gluteus medius level, 45 postmortem and ultimate pH (measured at 24-h postmortem) in m. longissimus lumborum and semimembranosus; meat colour; drip losses and intramuscular fat content in a m. longissimus sample. Five categories of pork products produced at large scale in Europe were considered in the study: fresh meat, cooked products, dry products, specialties and other meat products. For each of the studied farming systems, the technological meat quality requirements, as well as the market shares for each product category within farming system, were obtained from the literature and personal communications from experts. The tool resulted in an overall conformity score that enabled to discriminate among systems according to the degree of matching of the achieved carcass and meat quality with the requirements of the targeted market. In order to improve feasibility, the tool was simplified by selecting ultimate pH at m. longissimus or semimembranosus, minimum fat thickness measured at the left half carcass over m. gluteus medius and intramuscular fat content in a m. longissimus sample as iceberg indicators. The overall suitability scores calculated by using both the complete and the reduced tools presented good correlation and the results obtained were similar. The tool could be considered as robust enough to discriminate among different systems, since it was tested in a wide range of them. It also can be used to detect improvement opportunities to enhance sustainability of pig farming systems. The final objective of the study was achieved, since the market suitability tool could be used in an integrated sustainability analysis of pig farming systems.